2008
DOI: 10.1213/ane.0b013e318184d6c3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxygen Administration Improves Cerebral Oxygenation in Patients Undergoing Awake Carotid Surgery

Abstract: With the carotid cross-clamped, ipsilateral rSO2 was reliably increased by the administration of 100% O(2) compared with 28% O2. The etiology of this increase is unclear, but may relate to the associated increase in O2 content of the blood or to an improvement in cerebral blood flow. Thus administration of 100% O2 during carotid cross-clamping may be beneficial for all patients undergoing CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
0
22
0
5
Order By: Relevance
“…5,6 Increasing F io 2 during carotid endarterectomy with regional anesthesia has also been reported to reverse neurological deficits seen with carotid cross clamp placement. 25 Our results are consistent with these data as well as with findings from the static comparison of two P etco 2 ranges in the beach chair position; 13 rSO 2 was better preserved with fewer cerebral desaturation events at the higher P etco 2 range.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…5,6 Increasing F io 2 during carotid endarterectomy with regional anesthesia has also been reported to reverse neurological deficits seen with carotid cross clamp placement. 25 Our results are consistent with these data as well as with findings from the static comparison of two P etco 2 ranges in the beach chair position; 13 rSO 2 was better preserved with fewer cerebral desaturation events at the higher P etco 2 range.…”
Section: Discussionmentioning
confidence: 98%
“…The first measurement in the beach chair position (set point two) was obtained either, 1) 15 minutes after positioning, allowing the maximal decrease in rSO 2 to occur, 8 or 2) immediately if cerebral desaturation (defined as absolute value rSO 2 < 55% or a decrease from baseline of ≥ 20%) was sustained for ≥ 3 minutes in either hemisphere. Since the change in rSO 2 is typically complete and stable within 5 minutes following a change in inspired gas composition, 5 rSO 2 was recorded as a ‘snap shot’ after a minimum of 5 minutes at each subsequent set point. All cerebral desaturation events (absolute value rSO 2 < 55% or a decrease from baseline of ≥ 20% sustained for ≥ 3 minutes) were recorded and communicated by the clinical coordinator to allow intervention as deemed appropriate by the anesthesiologist: exclude and treat hypotension, exclude and treat excessive depth of anesthesia, move to the next ventilation set point if that included increasing F io 2 or P etco 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 It has also been shown that breathing 100% oxygen under these circumstances can result in clinical improvements in the neurologic deficit as a result of increased cerebral oxygen saturation in the affected area. 23 …”
Section: Carotid Endarterectomymentioning
confidence: 99%
“…27 By 2007, surgical fires occurred frequently enough to become mainstream news and were more common than was generally assumed. 28 Despite half a decade of effort since 2003 to disseminate best practices for preventing surgical fires, peer-reviewed articles such as Stoneham et al 30 still advocated unsafe operating room practices. For example, Zheng and Gravenstein 29 specifically expressed concern that the method of carotid cross-clamping proposed by Stoneham et al, 30 particularly for the up to 1 hour duration they described, might increase the likelihood of an oxygen concentration greater than 30% in the surgical field, 29,30 in direct contradiction to many widely circulated safety protocols.…”
mentioning
confidence: 99%